Notification of the counterparty of unilateral withdrawal from the agreement - Yu. I. Chalyi (Bulletin of Kharkiv National University of Internal Affairs)
The study focuses on the issue of notification of the initiator of unilateral withdrawal from a contract to its counterparty of such withdrawal. In particular, the problematic issues of determining the form and procedure for such notification and establishing the time when an agreement unilaterally withdrawn by one of its parties will be considered amended or terminated are considered. Current civil law does not provide clear answers to these questions. The necessity of differentiating the legislative rules which will determine the procedure for informing the interested party of the unilateral withdrawal from a contract by the other party, and also establish the moment when the legal consequences caused by unilateral withdrawal from a contract come into force, is pointed out. The criteria for such differentiation are the subject matter and type of contractual relationship, as well as the reasons for withdrawal from the contract, i.e. whether it arose due to a breach of contract by the counterparty or is related to other reasons. When the withdrawal is caused by a breach of contract, the injured party generally does not have to notify the offending party in advance of its intention to unilaterally withdraw from the contract. It is acceptable to give notice after the fact, but with the obligatory immediate notification of the offender or within another reasonable time. In the case of withdrawal for other reasons, the initiator of the withdrawal must usually inform its counterparty in advance. In the latter case, the notice of withdrawal has the form of a warning in the proper sense of the word.